Practitioner research in early childhood international issues and perspectives - Newman, Linda; Woodrow, Christine (Los Angeles SAGE, 2015)
"Bringing together theory and practice, this book draws on the projects and experiences of senior and new researchers implementing various forms of practitioner research. Chapter discussions are informed by international literature to provide insightful reflections on research processes and the contribution of practitioner research to changing practice. The diversity of perspectives across the chapters provides an excellent resource for those undertaking research within early childhood contexts. Topics discussed include: the contribution of practitioner research to curriculum and social change; professional development and strengthening learning communities; how practitioners can be supported in documenting and articulating their work; the relationships between the research community and field of practice through practitioner research projects; contemporary problems and issues that frame the practices of early childhood educators; case studies from Australia, South Africa, Swede and Chile." -- Back cover.
1. Recognising, valuing and celebrating practitioner research / Christine Woodrow and Linda Newman -- 2. Collaborative capacity building in early childhood communities in Chile / Linda Newman, Christine Woodrow, Silvia Rójo and Mónica Galvez -- 3. Insider Islamic spaces of inquiry: Muslim educators producing new knowledge in Sydney, Australia / Oznur Aydemir, Fatima Mourad, Leonie Arthur and Jen Skattebol -- 4. What is play for, in your culture? Investigating remote Australian Aboriginal perspectives through participatory practitioner research / Lyn Fasoli and Alison Wunungmurra -- 5. Developing collaboration using mind maps in practitioner research in Sweden / Karin Rönnerman -- 6. Reconceptualising services for young children through dialogue in a South African village / Norma Rudolph and Mary James -- 7. Sustaining curriculum renewal in western Sydney: three participant views / Linda Newman, Janet Keegan and Trish Heeley -- 8. (In)sights from 40 years of practitioner action research in education: perspectives from the US, UK and Australia / Nicole Mockler and Ashley Casey.
Includes bibliographical references and index.
Keywords: Early childhood education -- Research